(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This thesis discusses the harmony of physical and psychological training in preparing young volleyball athletes. Along with physical qualities, psychological factors such as motivation, self-confidence, and stress resistance play an important role in achieving high performance. The combined use of physical load and psychological training during practice increases athletes’ stability in competitions.